Pengaruh Tangibility, Profitabilitas, Pertumbuhan Perusahaan, Non Debt Tax Shields, Cash Holding dan Ukuran Perusahaan terhadap Struktur Modal Perusahaan (Studi pada Perusahaan Manufaktur yang Listing di BEI Tahun 2010-2012) - Widodo, Moch. Wahyu; Moeljadi; Djawahir, Achmad Helmy (Jurnal Aplikasi Manajemen, 2014)
This study purposed to examine the effect of variable tangibility, profitability, growth, non-debt tax shields, cash holding and firm size on their capital structure of manufacturing company in Indonesia. The multiple regression analysis is used to analyze the data in this study. Data analysis are implied on manufacturing company which listed on Indonesia Stock Exchange in periode 2010-2012. A total of 72 companies met the criteria as population of study, all members of the population used as sample. The results of this study indicate that the increasing of tangibility will increase the company's capital structure, the high level of profit company has low levels of debt, and company size affect the size of the company's capital structure, while, there no significant effect was found between the company growth, non-debt tax shields and cash holdings to their capital structure.